Research on application of tumor treating fields in glioblastoma: A bibliometric and visual analysis - Du, Xue; Chen, Chunbao; Xiao, Yu; Cui, Yu; Yang, Lu; Li, Xiaochun; Liu, Xueping; Wang, Ruisi; Tan, Bangxian (Frontiers in Oncology, 2022)
Background: Glioblastoma, one of the common tumors of the central nervous system (CNS). As an innovative physiotherapy method emerging in recent years, the tumor treating fields (TTFields) technique has been approved for the treatment of glioblastoma due to its non-invasive and portable features. The purpose of this study is to visualize and analyze the scientific results and research trends in TTFields therapy for glioblastoma. Methods: Publications related to TTFields therapy for glioblastoma were searched in the Web of Science Core Collection (WoSCC) database in September 2022. A bibliometric and visual analysis of publications in this field was performed mainly using CiteSpace and R software for country/region, author, journal, reference and keyword. Results: A total of 618 publications in this field were retrieved. The cumulative number of publications increased year by year, with an average growth rate (AGR) of 28.50%. The USA had the largest number of publications (123, 49.60%). As for the country/region collaborations, the USA cooperated most closely with other countries/regions, followed by Germany and China. The degree of collaboration (DC) between countries/regions was 25.81%. The institutions with the largest number of publications were Tel Aviv Univ (10), Harvard Med Sch (10) and Novocure Ltd (10). Moreover, Wong E (18) possessed the greatest number of publications. The DC between authors was 97.58%. STUPP R (236) was the most cited author. JOURNAL OF NEURO-ONCOLOGY (22) was the journal with the largest number of published publications (75). The top 10 keywords that occurred frequently included glioblastoma (156), tumor treating field (152), temozolomide (134), randomized phase Ⅲ (48), brain (46), survivor (46), cancer (44), trial (42), alternating electric field (42) and radiotherapy (36). Furthermore, cluster analysis was performed on the basis of keyword co-occurrence, and finally 15 clusters were formed. Conclusion: TTFields has been increasingly known as the fourth novel physical anti-tumor therapy in addition to surgery, radiotherapy and anti-tumor drugs. Cooperation and communication between countries/regions need to be enhanced in future research. Several studies have demonstrated the therapeutic potential of TTFields in glioma, and its application alone or in combination with other treatments has become a current research hotspot.